Report on visit to East and Southern Africa. April 4 - June 14, 1986 - Hetzel, D.J.S. (1986)
The three aspects of breed performance assessment considered evaluation as purebreds, evaluation of (F1) crosses with other breeds and evaluation as part of composite breeds. Performance evaluation were made for the indigenous African breeds, via Boran, Angoni, Tuli, Africander, Mashona and Tswana in Kenya, Uganda, Zimbabwe, Botswana and Zambia. The objective of the visit was to make recommendations on the need for future breed evaluation studies in Africa and on the scope of greater utilization of indigenous breeds.